THE LINGUODIDACTIC SIGNIFICANCE OF USING CULTURAL REALIA IN TEACHING THE UZBEK LANGUAGE TO FOREIGNERS (Journal of Multidisciplinary Sciences and Innovations, 2026)
In teaching a language as a foreign language, it is not sufficient to develop only grammatical and lexical competencies; it is also essential to explain the language within its cultural context. The use of cultural realia in teaching the Uzbek language to foreigners possesses particular scientific and practical significance. The study employed descriptive-analytical, comparative, and linguocultural methods. In addition, educational materials, authentic texts, audio-video resources, and situational exercises developed on the basis of experience in teaching Uzbek to foreign learners were analyzed. The findings of the research demonstrated that integrating cultural realia—such as customs and traditions, speech etiquette, national values, and social relations—into the educational process significantly enhances foreign learners’ language acquisition. A teaching model based on cultural realia has proven to be effective in teaching Uzbek as a foreign language.